The Roles Of Open Innovation As A Moderator And Corporate Sustainability As A Mediator In The Relationship Between Risk Management Factors And Financial Performance - Zaidan, Al Abboodi Ali Shakir (2024)
Crisis management is based on a combination of open innovation and corporate sustainability. The literature on crisis management confirms that investigation of such a strategy is often limited. With the uncertainty that risk management factors (crisis proneness, risk-taking, knowledge of the crisis, decision making and crisis management) are active in corporate sustainability and financial performance. Many challenges and open issues facing the achievement of crisis management have not been observed yet. This study aims to explore the impact of risk management factors on financial performance through the mediating variable, corporate sustainability. In addition, The study explores the strength of the relationship between risk management factors and corporate sustainability through the interaction of open innovation. To this end, this study supplements the academic literature with an integration of partial least squares structural equation modeling (PLS-SEM).